Quantification of pro-vitamin a activities and content in 22 selected ‘ULAM’ species or Malaysian traditional vegetables - Mohd Zaifuddin, Fatimah Azzahra; Mohd Hassan, Norazian; Othman, Rashidi (Academic Sciences, 2014)
Recently there is a considerable interest in combating vitamin A deficiency (VAD) by manipulating carotenoid content and composition in plants through genetic manipulation to meet the daily requirements for vitamin A. In Malaysia and most developing countries many people survive largely on plant-based diets or monotonous consumption such as cereals and legumes that are poor sources of vitamin A. Ulam or traditional vegetables consumed by Malaysian comprise more than 120 species representing various plant leaves, fruits, seeds, tubers and roots are valuable sources of nutrients and pro-vitamin A. These pro-vitamin A compounds can profoundly protect our well-being or risk of disease throughout our lives. Therefore, identifying nutritional quality of food crops and its ingredients for VAD is one of the urgent health issues and research worldwide. This study established that traditional vegetables or ulam differ greatly with respect to types and concentrations of pro-vitamin A. A total of 22 ulam species were evaluated for quantitative and qualitative pro-vitamin A composition through HPLC analysis. Three main pro-vitamin A carotenoids were identified namely β-cryptoxanthin, α-carotene and β-carotene. These pro-vitamin A groups content and ratio varies between ulam species but were detected higher in cekur manis (68.44±0.23 μg/g DW), pegaga (2142.71±11.70 μg/g DW) and daun selom (3085.02±5.87 μg/g DW). Total retinol equivalent activity presented by these pro-vitamin A groups in every ulam species demonstrated that beluntas has the highest activity (656.59 μg/g DW). The information gathered in this study embarked that almost all of the ulam species are good and potent sources of pro-vitamin A.